Analisis Kinerja Ruas Jalan HOS Cokroaminoto Akibat Perkembangan Lalu Lintas di Yogyakarta - Gustav, Reza (Jurnal Semesta Teknika, 2012)
Yogyakarta is a region with high traffic. It also has high population density. These matters have been predicted to cause transportation problems. HOS Cokroaminoto Street, as a road in urban city center, has the potential to have such problems. Analysis and evaluation needs to be done to maintain good performance of the road. Manual Kapasitas Jalan Indonesia 1997 is used to measure the performance of traffic which includes operational analysis and the planning of urban roads. Level of Service Criteria (LSC) is determined based on the regulation of The Ministry of Transportation KM No. 14 of 2006. Traffic data had been obtained by counting the number of vehicles for 3 days on the busy-hour. These data were presented in tabular data of the vehicle, and then the performance of the traffic was analyzed. For urban roads, form UR-1, UR-2, and UR-3 (MKJI 1997) are used. Based on the results of the performance analysis on HOS Cokroaminoto Street with MKJI 1997 method, in 2010, the degree of saturation (DS) of the road is 0.43. It means that, in LSC term, this road is in level B. It is predicted that, in 2016-2020, this road will not satisfy the eligibility standard (DS> 0.75). This shows that the performance improvement of HOS Cokroaminoto Street is required. From the alternative solutions, the scenario of side friction reduction is more rational to maintain the eligibility and performance of HOS Cokroaminoto Street.